Tracking pollutant emissions. Issue 12 (December 2017) - Gentner, Drew; Xiong, Fulizi
Progress in the post-combustion treatment of diesel vehicle exhaust has led to shifting proportions of the constituents of nitrogen oxides. Observations from 61 European cities suggest that the outlook on attaining NO2 standards is more optimistic than expected.